Pengaruh Harga, Kualitas Produk, dan Citra Merek Terhadap Keputusan Pembelian Konsumen Motor Honda di Kecamatan Banjarsari Surakarta - Firgiawan Krisna Saputra; Sumaryanto (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study is a survey of Honda motorcycle consumers in Banjarsari District, Surakarta. The aim of this study is to analyze the influence of price, product quality, and brand image on purchasing decisions of Honda motorcycle consumers in Banjarsari District, Surakarta. The research problem stems from the increasingly fierce competition in the automotive industry, particularly in the two-wheeled vehicle segment, requiring manufacturers to understand the factors that influence consumer purchasing decisions. This research is quantitative. The population in this study was Honda motorcycle consumers in Banjarsari District, with a sample size of 100 respondents determined using the Slovin formula. Data collection was conducted using a questionnaire with a Likert scale. Data analysis used validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results showed that price had no significant effect on purchasing decisions, product quality had a significant effect on purchasing decisions, and brand image had a significant effect on purchasing decisions. Simultaneously, price, product quality, and brand image significantly influenced consumer purchasing decisions. The Adjusted R² value of 0.435 shows that the three independent variables are able to explain purchasing decisions by 43.5%, while the remaining 56.5% is influenced by other factors outside the research model.